ANALISIS ISI USUS IKAN TEMBANG (Sardinella fimbriata) PADA PERAIRAN PANTAI LABU KABUPATEN DELI SERDANG SUMATERA UTARA Gut Contents Analysis of Tembang Fish (Sardinella fimbriata) at Labu Beach Waterway Deli Serdang Regency North Sumatera - Rebeka Paimaibot S; Yunasfi Djayus; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
This study aims to investigate food habits of the species of tembang fish (Sardinella fimbriata) and the relationship of water quality parameters with the availability of natural food in Labu Beach. The study was done from Juli 2014, in Labu Beach. Fish samples, collected by gill net. Stomach content was analyzed using Index of preponderance. Stomach contents of the fish was consisted of 6 class of food Bacillariophyceae, Chlorophyceae, Dinophyceae, Crustaceae, fish’s egg and added some unidentified (such as foot and the cutting of insect body). The group of Bacillariophyceae is a main food, Chlorophyceae, Crustaceae and unidentified group is a complement food and than Dinophyceae and fish’s egg as additional food. The natural food has a good correlation with brightness.Keywords: Fish’s intestines contents, Sardinella fimbriata, Labu Beach, Gill Net.